The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1136/jnnp.46.8.751
|View full text |Cite
|
Sign up to set email alerts
|

Change of seizure frequency in pregnant epileptic women.

Abstract: SUMMARY The effect of pregnancy on seizure frequency was monitored prospectively in 136 pregnancies of 122 epileptic women. Pregnancy did not influence the seizure frequency in 68 pregnancies (50%). In 50 pregnancies (37%) the number of seizures increased during pregnancy or puerperium. The seizure frequency decreased in 18 pregnancies (13%). In 34 out of 50 pregnancies (68%) the increase was associated with non-compliance with the drug regimen or sleep deprivation. In seven out of 18 pregnancies (39%) improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
55
1
9

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 5 publications
4
55
1
9
Order By: Relevance
“…16 Observations of pregnant women with epilepsy taking a variety of AEDs indicate that approximately 17% to 37% of patients will have an increase in their seizures, 7% to 25% will have a decrease in seizures, and 50% to 83% will experience no significant change. 21,24 Most of these investigations have implicated subtherapeutic AED concentrations as a contributor to increased seizures during pregnancy. 16,[22][23][24] Generalized tonic-clonic seizures (GTC-Szs) are considered the most dangerous [25][26][27][28][29] and may even increase the risk for cognitive dysfunction in the offspring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Observations of pregnant women with epilepsy taking a variety of AEDs indicate that approximately 17% to 37% of patients will have an increase in their seizures, 7% to 25% will have a decrease in seizures, and 50% to 83% will experience no significant change. 21,24 Most of these investigations have implicated subtherapeutic AED concentrations as a contributor to increased seizures during pregnancy. 16,[22][23][24] Generalized tonic-clonic seizures (GTC-Szs) are considered the most dangerous [25][26][27][28][29] and may even increase the risk for cognitive dysfunction in the offspring.…”
mentioning
confidence: 99%
“…21,24 Most of these investigations have implicated subtherapeutic AED concentrations as a contributor to increased seizures during pregnancy. 16,[22][23][24] Generalized tonic-clonic seizures (GTC-Szs) are considered the most dangerous [25][26][27][28][29] and may even increase the risk for cognitive dysfunction in the offspring. 30,31 The alterations in LTG Cl during pregnancy have important clinical relevance.…”
mentioning
confidence: 99%
“…В литературе также приводят данные, согласно которым ухудшение течения эпилепсии в период беременности было связано с нарушением комплайентности к терапии или депривацией сна [7,10,11]. Правильная подготовка женщины к пред-стоящей беременности, хороший контроль пациенток, отсутствие припадков, по край-ней мере, за 3 мес до беременности, достиг-нутые коррекцией неадекватной терапии до беременности, недостаточной комплай-ентности и депривации сна, способствуют уменьшению частоты припадков во время беременности [12,13].…”
unclassified
“…В то же время в некоторых случаях не-возможно объяснить причину улучшения течения эпилепсии при беременности, и оно может быть связано со случайной флюктуа-цией частоты припадков или другими фак-торами (например, гормональными измене-ниями) [11]. У 1 (1,4±1,4%) женщины после внезапно-го прекращения приема АЭП (карбамазепи-на) во время беременности зарегистрирован генерализованный судорожный эпилепти-ческий статус на 14-15-й неделях.…”
unclassified
“…Since oestrogens are known to be epileptogenic [7], pregnancy could reduce seizure threshold in a patient already harbouring a chronic, sub-clinical encephalitic pro cess. However, in patients with established epilepsy pregnancy does not have a consistent effect on seizure control, but if worsening does occur, this is most likely in the first trimester [8], Alternatively, the depression of cell-mediated immunity in pregnancy could facilitate primary viral infection or reactivation of latent infection with cyto megalovirus [6] or Epstein-Barr virus [9], both of which have been implicated in the encephalitic process underlying Rasmussen's syn drome. Moreover, it has been reported that alpha interferon, an agent with both immunomodulatory and antiviral activities, may improve both the seizure frequency and neurological deficit in Rasmussen's syndrome [10].…”
mentioning
confidence: 99%